IMPLEMENTASI MEDIA SOSIAL UNTUK EDUKASI STANDAR PROKES ANAK DIBAWAH UMUR DI DESA PEMECUTAN KLOD - Paranegara, Y. V.; Basmantra, I. N. (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
The majority of COVID-19 immunizations are administered to adults, while vaccinations for children aged 0 to 17 years are still rare. Despite the fact that vaccination has been highlighted, there are still adults who have only got the first dosage, the first and second doses, and others who have not. As a result, children are at risk of contracting COVID-19 from their parents. Discipline of children and parents in the form of wearing masks, keeping social distance, and preserving cleanliness in the implementation of health care requirements. In addition, there is a lack of understanding about the need of establishing standard processes to limit risk and prevent the spread of COVID-19. In the period of the COVID-19 pandemic, social media has evolved into a learning tool. In addition to providing enjoyment, social media may be utilized as an alternative source of answers to common concerns, such as information and queries concerning the COVID-19 viral infection. Instagram is the social media platform utilized, and there is intriguing material in the form of entertaining videos and photographs, as well as an operating system that is simple for youngsters to use. Implementation of social media accounts that share the most up-to-date information about COVID-19 and interesting health care standards so that children are not bored and can socialize directly with children in the Monang Maning area, Pemecutan Klod Village, Denpasar as an initial step in the dissemination of social media accounts. Through this strategy, the Instagram account formed has shown to be helpful in raising awareness of COVID-19 among children and parents, as well as being more disciplined in adopting health protocol criteria for attempts to minimize COVID-19 dissemination.     Keywords: Social Media, Kids, Standard Health Protocol